Scotland : the making and unmaking of the nation, c.1100-1707. - Harris, Bob, 1964-; MacDonald, Alan R., 1969- (Dundee University Press, 2006)
Scotland: The Making and Unmaking of the Nation, c.1100-1707 aims to show the importance of Scotland's relationships to Europe and its part in a broader European story, as well as to dispel long-established myths and preconceptions which continue to exert a firm grip on public opinion. Especially in a post-devolution era, Scottish history and Scotland deserve better than this.Scotland: The Making and Unmaking of the Nation, c.1100-1707 is certainly designed to provoke but need not be taken to indicate a nationalist view of 1707 as a moment of eclipse. Scotland's history, like all histories, resists simple generalisations. Were it otherwise, its study would not be so rewarding.